Absolute music and the construction of meaning - Chua, Daniel K. L., 1966- (New perspectives in music history and criticism., 1999)
This book examines the intellectual history of instrumental music, particularly the idea of absolute music. It shows how certain ideas in philosophy, theology and the sciences affect the meaning of instrumental music, and how instrumental music in turn permeates human discourse and helps construct meaning.